The Effect of Wharton Jelly-Derived Mesenchymal Stromal Cells and Their Conditioned Media in the Treatment of a Rat Spinal Cord Injury - Milada Chudickova (International Journal of Molecular Sciences, 2019)
The transplantation of Wharton’s jelly derived mesenchymal stromal cells (WJ-MSCs) possesses therapeutic potential for the treatment of a spinal cord injury (SCI). Generally, the main effect of MSCs is mediated by their paracrine potential. Therefore, application of WJ-MSC derived conditioned media (CM) is an acknowledged approach for how to bypass the limited survival of transplanted cells. In this study, we compared the effect of human WJ-MSCs and their CM in the treatment of SCI in rats. WJ-MSCs and their CM were intrathecally transplanted in the three consecutive weeks following the induction of a balloon compression lesion. Behavioral analyses were carried out up to 9 weeks after the SCI and revealed significant improvement after the treatment with WJ-MSCs and CM, compared to the saline control. Both WJ-MSCs and CM treatment resulted in a higher amount of spared gray and white matter and enhanced expression of genes related to axonal growth. However, only the CM treatment further improved axonal sprouting and reduced the number of reactive astrocytes in the lesion area. On the other hand, WJ-MSCs enhanced the expression of inflammatory and chemotactic markers in plasma, which indicates a systemic immunological response to xenogeneic cell transplantation. Our results confirmed that WJ-MSC derived CM offer an alternative to direct stem cell transplantation for the treatment of SCI.